Prediction of Pinostrobin Pharmacokinetics from Temu Kunci (Boesenbergia rotunda (L.) Mansf.) Using pkCSM - Faisal Akhmal Muslikh; Anis Akhwan Dhafin; Fendy Prasetyawan (Contemporary Journal of Applied Sciences, 2023)
Indonesia is a megabiodiversity country with the second-largest abundance of biodiversity in the world. Temu kunci (Boesenbergia rotunda (L.)) is a well-known traditional medicinal plant in Indonesia with many nutritional and therapeutic benefits. It is known to have good pharmacological activity, which is due to the content of secondary metabolites commonly known as pinostrobin. However, more scientific data is still needed to justify its increased use, especially regarding its pharmacokinetics and safety. The aim of the research was to predict the pharmacokinetic properties of pinostrobin compounds. The pinostrobin compound was obtained from PubChem, accessible at https://pubchem.ncbi.nlm.nih.gov/, and then pharmacokinetic analysis was carried out using a web tool (https://biosig.lab.uq.edu.au/pkcsm/prediction). The research results show that the pinostrobin compound is a compound that has pharmacokinetic properties, showing that this compound has poor distribution and toxicity capabilities.